Kingdom, State and Civil Society in Africa - Kasfir, Nelson (Carl Schlettwein lectures, 2018)
Civil society is one of several Western political and social concepts that have not traveled successfully to Africa. Revived in response to the search for democracy in Eastern Europe during the late Soviet era, Western donors promoted and funded new civil society organizations in sub-Saharan Africa, regarding them as an essential grounding for African democratization. Most of these new civil society organizations had little in common with African associational activity. Focusing on the characteristics and behavior of long-standing African organizations would appear a better starting point for developing a useful concept of an African civil society. One candidate worth serious investigation is the Buganda Kingdom Government. This organization violates most distinctions central to Western notions of civil society. Yet it continues to behave like a civil society organization. Its political and conceptual collisions offer guidance toward a useful notion of African civil society and understanding Ugandan politics.